KINERJA KEUANGAN, CORPORATE SOCIAL RESPONSIBILITY, NILAI PERUSAHAAN, DAN GOOD CORPORATE GOVERNANCE - Edi Wibowo, Mariatun, Untung Sriwidodo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
Manufacturing companies that transform raw materials into finished productsthrough the production process. This research uses the manufacturing companies sectorfor many manufacturing companies causing environmental efects in their productionprocesses. The purpose of research is to analyze the significance of the effect of thefinancial performance and Corporate Social Responsibility (CSR) to corporate valueand Good Corporate Governance (GCG) strengthening or moderating financialperformance and CSR on firm value. In conclusion that the financial performancesignificantly influence on firm value, CSR no significant influence on firm value andGCG not moderate financial performance and CSR influence on firm value. The resultsof the analysis of the coefficient of determination is obtained is known that the influenceexerted by the independent variable of financial performance and CSR of the dependentvariable is firm value with a moderating variable is GCG is 24,3% while the rest(100% - 24,3%) = 75,7% influenced by other factors beyond the variables studied.Keywords: financial performance, Corporate Social Responsibility, firm value, GoodCorporate Governance